2018
DOI: 10.1021/acs.est.8b01885
|View full text |Cite
|
Sign up to set email alerts
|

Linking Microbial Activities and Low-Molecular-Weight Thiols to Hg Methylation in Biofilms and Periphyton from High-Altitude Tropical Lakes in the Bolivian Altiplano

Abstract: The sources and factors controlling concentrations of monomethylmercury (MMHg) in aquatic ecosystems need to be better understood. Here, we investigated Hg transformations in sediments, periphyton associated with green algae's or aquatic plants, and benthic biofilms from the Lake Titicaca hydrosystem and compared them to the occurrence of active methylating microorganisms and extracellular Hg ligands. Intense Hg methylation was found in benthic biofilms and green algae's periphyton, while it remained low in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 72 publications
5
65
1
Order By: Relevance
“…Although MMHg is also low in concentration, a striking feature is a high percentage in MMHg which rises up to 20% while in non-contaminated surface waters around the globe it generally stands around 1-2%. As discussed in a previous publication [57], these high MMHg percentages can be explained by (i) high MMHg production in an environment favorable to methylating micro-organisms (e.g., sulfate-rich water and sediment, lower dissolved oxygen levels, neutral to alkaline water, shallow areas, et al) [92], (ii) stabilization and accumulation of MMHg in waters due to abundant (in)organic ligands [105], and (iii) low degradation of MMHg in organic-rich waters.…”
Section: Enhanced Methylmercury Concentration In Surface Water Duringmentioning
confidence: 83%
See 3 more Smart Citations
“…Although MMHg is also low in concentration, a striking feature is a high percentage in MMHg which rises up to 20% while in non-contaminated surface waters around the globe it generally stands around 1-2%. As discussed in a previous publication [57], these high MMHg percentages can be explained by (i) high MMHg production in an environment favorable to methylating micro-organisms (e.g., sulfate-rich water and sediment, lower dissolved oxygen levels, neutral to alkaline water, shallow areas, et al) [92], (ii) stabilization and accumulation of MMHg in waters due to abundant (in)organic ligands [105], and (iii) low degradation of MMHg in organic-rich waters.…”
Section: Enhanced Methylmercury Concentration In Surface Water Duringmentioning
confidence: 83%
“…High sulfate levels in the systems that prompt SRB dominance under low oxygen conditions, as shown by the high H 2 S concentrations, may explain the observed increase of MMHg in the water [92]. SRB are the main Hg methylators at Titicaca Lake [105]. However, several studies have suggested that blooms may reduce MMHg concentrations in algae by a biomass growth dilution effect and have shown observationally [106] and experimental data [6,7,107] to support such a hypothesis.…”
Section: Enhanced Methylmercury Concentration In Surface Water Duringmentioning
confidence: 96%
See 2 more Smart Citations
“…They are recognized to participate in the transformations of Hg in natural waters. Indeed, bioaccumulated IHg has been demonstrated to be reduced into its elemental Hg 0 form by biofilms [12] as well as methylated by inhabiting sulfate-reducing bacteria, iron-reducing bacteria, and methanogens whereas demethylation of MeHg has been also shown to occur [13][14][15].…”
Section: Introductionmentioning
confidence: 99%